1970
DOI: 10.3329/bmrcb.v34i2.1178
|View full text |Cite
|
Sign up to set email alerts
|

Use of anthropometric indicators for predicting risk of delivering low birth weight babies

Abstract: DOI: 10.3329/bmrcb.v34i2.1178Bangladesh Med Res Counc Bull 2008; 34: 64-66

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Six longitudinal studies that measured MUAC during antenatal visits also reported MUAC as predictor of LBW in pregnant women, similar to the current study. All the six found significantly increased risk of LBW among mothers with low MUAC during pregnancy (Frison et al, 2016;Sebayang et al, 2012;Assefa, Berhane, & Worku, 2012;Mohanty et al, 2005;Kelly et al, 1996;Karim & Mascie-Taylor, 1997 (Dhar & Bhadra, 2008;Elshibly & Schmalisch, 2008;Sebayang et al, 2012). LBW or SGA babies are not only at greater risk of dying than infants of average weight but also at risk of more frequent infections and impaired cognitive development and are more likely to become undernourished children and adolescents (Saugstad, 1981).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Six longitudinal studies that measured MUAC during antenatal visits also reported MUAC as predictor of LBW in pregnant women, similar to the current study. All the six found significantly increased risk of LBW among mothers with low MUAC during pregnancy (Frison et al, 2016;Sebayang et al, 2012;Assefa, Berhane, & Worku, 2012;Mohanty et al, 2005;Kelly et al, 1996;Karim & Mascie-Taylor, 1997 (Dhar & Bhadra, 2008;Elshibly & Schmalisch, 2008;Sebayang et al, 2012). LBW or SGA babies are not only at greater risk of dying than infants of average weight but also at risk of more frequent infections and impaired cognitive development and are more likely to become undernourished children and adolescents (Saugstad, 1981).…”
Section: Discussionmentioning
confidence: 97%
“…Although recognized earlier, the importance of MUAC in predicting BW was first published by Lechtig () in a study comparing MUAC and other conventional high‐risk anthropometric indicators during pregnancy for LBW assessment in Guatemala. Being simple and cost‐effective, MUAC was rapidly promoted as an indicator for risk of LBW baby by many longitudinal and cross‐sectional studies (Dhar & Bhadra, ; Elshibly & Schmalisch, ; Sebayang et al, ). LBW or SGA babies are not only at greater risk of dying than infants of average weight but also at risk of more frequent infections and impaired cognitive development and are more likely to become undernourished children and adolescents (Saugstad, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Frequently monitoring of MUAC of pregnant women could serve as a simple proxy indicator for identifying infants at risk of growth faltering and stunting. Compared with body mass index, MUAC is a better measurement to determine nutritional status during pregnancy (Dhar & Bhadra, 2008;Elshibly & Schmalisch, 2008;Ogbonna et al, 2007;Sebayang, Dibley, Kelly, Shankar, & Shankar, 2012;Sen, Roy, & Mondal, 2010). Furthermore, MUAC is an easy method to use and does not require sophisticated equipment.…”
Section: Discussionmentioning
confidence: 99%